Use of library resources and services by part time undergraduates in Olabisi Onabanjo university, Ogun State, Nigeria - Oyedipe, Janet W; ADEKUNMISI, Ronke S (University of Dar es Salaam Library Journal, 2019)
This study investigated library resources and services use by part time undergraduates at Olabisi Onabanjo University, Nigeria. A survey research design of ex-post-facto was adopted. Interviews and a validated questionnaire with a (Cronbach alpha reliability of 0.72) were used to collect data for the study. A simple random sampling technique was used to select 250 part time undergraduate respondents for the study. The questionnaire was administered to 250 part time undergraduates but only 200 copies were returned and found usable. The findings indicated that library resources such as, textbooks, reports, monographs, reference materials and so on were available and accessible to the students. Library services such as book loan services, reference service, Internet services and so on were also available and accessible. However, part time undergraduates considered textbooks, dictionaries and encyclopedia as the most relevant of the library resources. Furthermore, dictionaries, newspapers, magazines and textbooks were found to be the most accessible of all the library resources surveyed. In view of this, an integration of teachable information literacy into academic curricula of part time learners, use of ICT and social media tools and aggressiveness in resources and services provision and functions of the library and librarians were recommended, amongst other suggestions. It was concluded that part time learners should have timely and quality access to scholarly information resources and services.